Project management in research and development - Jerzy Kisielnicki (Foundations of Management, 2014)
Implementation of R&D projects determines whether the organization is changing and becoming fully competitive. R&D projects are the basis for innovation policy at the macro level - the state - and the micro level - the organization. Management of R&D projects requires not only high level of skills, but knowledge of highly developed tools to support the development of the organization. In managing this type of project, methods such as management competence, talent and knowledge, knowledge of modern information, and communication technology, stand out. In this study the following issues are presented: analysis of decision-making processes of R&D projects, basic modeling methodology of R&D projects, and analysis of communication systems in project management. The final part of the article presents the problems of commercialization of results obtained from R&D projects.
Keywords: 650; R&D projects; decision in R&D projects; modeling of R&D projects; the system of communication in the project; the project managers; the commercialization of the project results